Antiamoebic Activity of Imidazothiazole Derivatives against Opportunistic Pathogen Acanthamoeba castellanii - Noor Akbar; Mohammed I. El-Gamal; Balsam Qubais Saeed; Chang-Hyun Oh; Mohammed S. Abdel-Maksoud; Naveed Ahmed Khan; Ahmad M. Alharbi; Hasan Alfahemi; Ruqaiyyah Siddiqui (MDPI AG, 2022)
We examined the antiamoebic effect of several imidazothiazole derivatives on Acanthamoeba castellanii of the T4 genotype. Trypan blue exclusion assays and haemocytometer counting were used to determine the reduction in A. castellanii trophozoite proliferation, in response to treatment with these compounds. To determine the effects of these compounds on host cells, lactate dehydrogenase assay was performed using HeLa cell lines. Amoebicidal assays revealed that the tested compounds at concentrations of 50 µM significantly inhibited amoebae trophozoites compared to controls. Compounds 1m and 1zb showed the highest amoebicidal effects eradicating 70% and 67% of A. castellanii, respectively. The compounds blocked both the encystation and excystation process in A. castellanii. Compounds 1m and 1zb blocked 61% and 55%, respectively, of amoeba binding to human cells. Moreover, the compounds showed minimal cytotoxic effects against host cells and considerably reduced amoeba-mediated host cell death. Overall, our study revealed that compounds 1m and 1zb have excellent antiamoebic potential, and should be considered in the development of curative antiamoebic medications in future studies. Further work is critical to determine the translational value of these findings.